2022
DOI: 10.3390/d14080672
|View full text |Cite
|
Sign up to set email alerts
|

Land Uses for Pasture and Cacao Cultivation Modify the Odonata Assemblages in Atlantic Forest Areas

Abstract: Tropical forests such as the Atlantic Forest are under constant threats from the impact of human activities, mostly being caused by the loss of native forest areas for other land uses. This study aimed to evaluate the effect of changes in land use for pasture and cacao cultivation on the richness and composition of Odonata assemblages in comparison to native forest areas. We also evaluated the species as possible indicators of these different land uses. In total, 64 streams were sampled in southern Bahia, Braz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Two articles in this section dealt with land use for pasture and cocoa cultivation in the Brazilian state of Bahia. The first one, entitled "Land uses for pasture and cacao cultivation modify the Odonata assemblages in Atlantic Forest areas" [17], investigates the effects of changes in land use on Odonata assemblages in the Atlantic Forest of Brazil. The study found that changes such the conversion of original forest areas to pasture significantly alter the richness and composition of Odonata assemblages.…”
Section: Ecologymentioning
confidence: 99%
“…Two articles in this section dealt with land use for pasture and cocoa cultivation in the Brazilian state of Bahia. The first one, entitled "Land uses for pasture and cacao cultivation modify the Odonata assemblages in Atlantic Forest areas" [17], investigates the effects of changes in land use on Odonata assemblages in the Atlantic Forest of Brazil. The study found that changes such the conversion of original forest areas to pasture significantly alter the richness and composition of Odonata assemblages.…”
Section: Ecologymentioning
confidence: 99%
“…They play a relevant ecological role as bioindicators of water quality and associated terrestrial ecosystems (Catling 2005; gonçalVes 2012). For example, the family Coenagrionidae becomes more frequent and abundant compared to other families of Zygoptera, as well as Libellulidae to other families of Anisoptera, in tropical forests of higher anthropic pressure (sigutoVá et al 2019), such as areas of pasture or cocoa cultivation, which promote modifications in Odonata communities compared to native areas (Santos & rodrigues 2022). Besides that, in the trophic levels, both larvae and adults are predators (Costa et al 2012;Fulan & anjos 2015;Vatandoost 2021) and also serve as prey for different taxa (Costa et al 2012;souza et al 2018).…”
mentioning
confidence: 99%